Gut eutrophication - Uzoigwe, Chika Edward (Frontiers in Microbiomes, 2024)
“Classical eutrophication” occurs when raw unfixed nutrients enter an aquatic environment. This causes the deleterious proliferation in fauna most adept at exploiting this abundance of nutrition. The net effect is de-diversification. We propose an analogous process in the gut: “gut eutrophication”. Evidence shows that consumption of processed food, high in unfixed disaccharides, causes an expansion of bacteria in the gut habitat with a metabolic proclivity for these nutrients. This is at the expense of microbiota with a predilection for complex macromolecule macronutrients. There is a loss of diversity and the effect is exacerbated by a sedentary lifestyle. Gut luminal low oxygen tension favors salubrious gut commensals. This effect is potentiated by exercise but thwarted by inactivity. Antibiotics cause an obvious gut dysbiosis. So too can diet in a more insidious manner. The transition in microbial composition, seen in “gut eutrophication”, may be an aetiological component of metabolic disease-associated gut dysbiosis.